Claustral colony founding does not prevent sensitivity to the detrimental effects of azole fungicides on the fecundity of ants. (15th February 2021) - Heneberg, Petr; Svoboda, Jakub; Pech, Pavel
Abstract: Azole fungicides (benzimidazoles, triazoles and imidazoles) are among the most widely used agrochemicals in the world. Unfortunately, azole fungicides are increasingly recognized for playing the role of endocrine disruptors in non-target organisms. Previously, the fecundity of ants with semi-claustral colony founding was found to be severely decreased in response to field-realistic concentrations of azole fungicides. However, during claustral colony founding, the ant queens do not feed and could therefore be protected against effects of agrochemicals applied during the colony founding. In the present study, we hypothesized that claustral colony founding is associated with a lower risk of oral exposure of ant queens to azole fungicides. We exposed queens of a common farmland ant species with claustral colony founding, Lasius niger, to four azole fungicides (epoxiconazole, flusilazole, prochloraz and thiophanate-methyl) that are commonly used in foliar applications and analyzed the differences in fecundity between fungicide-treated groups and the control water-treated group. We found that oral exposure to all four tested formulations of azole fungicides decreased the fecundity of L. niger queens. The decreases in fecundity ranged from 30.5% (epoxiconazole) to 40.3% (prochloraz), although the concentrations of fungicides used were several times lower than the minimum effective concentrations used to eliminate the target fungi by foliar applications of examined fungicides on various crops. Ants with both claustral and semi-claustral colony founding are highly vulnerable to field-realistic concentrations of azole fungicides that are sprayed in foliar applications. Azole fungicides substantially decrease the fitness of ant queens and may explain part of the recently observed decreases in farmland insect abundance and diversity. Graphical abstract: Image 1 Highlights: Azole fungicides are among the most widely used agrochemicals in the world. Ants are highly vulnerable to field-realistic concentrations of azole fungicides. Azole fungicides are endocrine disruptors in non-target organisms, such as ants. Azole fungicides have detrimental effects on the fecundity of ants. Azole fungicides should be replaced with safer alternatives.